2018
DOI: 10.1021/acsinfecdis.8b00244
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for the Interaction and Processing of β-Lactam Antibiotics by l,d-Transpeptidase 3 (LdtMt3) from Mycobacterium tuberculosis

Abstract: Targeting Mycobacterium tuberculosis peptidoglycans with β-lactam antibiotics represents a strategy to address increasing resistance to antitubercular drugs. β-Lactams inhibit peptidoglycan synthases such as L,D-transpeptidases, a group of carbapenem-sensitive enzymes that stabilize peptidoglycans through 3 → 3 cross-links. M. tuberculosis encodes five L,D-transpeptidases (Ldt Mt1−5 ), of which Ldt Mt3 is one of the less understood. Herein, we structurally characterized the apo and faropenem-acylated forms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…It is noteworthy that LDTs of the same bacterium might vary in their size and domains. For instance, Mycobacterium tuberculosis five LDTs (Ldt Mt1-5 ) have 30%-50% sequence identity, and four of them are structurally well characterized [53,[55][56][57][58]. Ldt Mt2 and Ldt Mt5 are significantly longer than Ldt Mt1 and Ldt Mt3 and possess an extra domain: the bacterial immunoglobulin-like domain BIgA [55].…”
Section: Structural Studies On Ldtsmentioning
confidence: 99%
“…It is noteworthy that LDTs of the same bacterium might vary in their size and domains. For instance, Mycobacterium tuberculosis five LDTs (Ldt Mt1-5 ) have 30%-50% sequence identity, and four of them are structurally well characterized [53,[55][56][57][58]. Ldt Mt2 and Ldt Mt5 are significantly longer than Ldt Mt1 and Ldt Mt3 and possess an extra domain: the bacterial immunoglobulin-like domain BIgA [55].…”
Section: Structural Studies On Ldtsmentioning
confidence: 99%
“…M.tb contains several paralogs of L,D -transpeptidases, namely Ldt Mt1 , Ldt Mt2 , Ldt Mt3 , Ldt Mt4 , and Ldt Mt5 ( Gupta et al, 2010 ). Crystal structures of Ldt Mt1 ( Correale et al, 2013 ), Ldt Mt2 ( Erdemli et al, 2012 ), Ldt Mt3 ( Libreros-Zúñiga et al, 2019 ), and Ldt Mt5 ( Brammer Basta et al, 2015 ) have been solved and reported to date. All of these paralogs contain a pocket similar to the S-pocket found in Ldt Mt2 .…”
Section: Discussionmentioning
confidence: 99%
“…Among the five L,D -transpeptidase paralogs of M.tb , Ldt Mt2 plays an important role since an M.tb strain lacking the gene encoding this enzyme exhibits attenuation in virulence and exhibits enhanced susceptibility to β-lactam antibiotics ( Bianchet et al, 2017 ; Brammer Basta et al, 2015 ; Dubée et al, 2012 ; Gupta et al, 2010 ; Libreros-Zúñiga et al, 2019 ; Sanders et al, 2014 ; Schoonmaker et al, 2014 ). Additional reports have demonstrated altered and attenuated cellular physiology of M.tb in association with the loss of function of Ldt Mt1 ( Schoonmaker et al, 2014 ) and Ldt Mt5 ( Brammer Basta et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The 3-3 linkages are generated by the more recently discovered enzyme class, the L,D-transpeptidases (Mainardi et al, 2005). Among the five L,D-transpeptidase paralogs of M.tb, LdtMt2 plays an important role since an M.tb strain lacking the gene encoding this enzyme exhibits attenuation of persistence and virulence (Bianchet et al, 2017;Brammer Basta et al, 2015;Dubee et al, 2012;Gupta et al, 2010;Libreros-Zuniga et al, 2019;Sanders et al, 2014;Schoonmaker et al, 2014). Additional reports have demonstrated altered and attenuated cellular physiology of M.tb in association with the loss of function of LdtMt1 (Schoonmaker et al, 2014) and LdtMt5(Brammer Basta et al, 2015).…”
Section: Introductionmentioning
confidence: 99%